Resultados do Tratamento do Linfoma de Burkitt com a Associação de Ciclofosfamida, Vincristina e Methotrexate - Moreira, Wagner Brant (2023)
Between march/81 to april/86 thirty-three Burkitt's Lymphoma patients were treated at our Instituition with combination Chemotherapy containing intravenous administration of Cyclophosphamide, Vincristine and Methotrexate and in trathecal injections of Methotrexate as described byZiegler in 1977. Patients median age was 7 years and the sex ratio (malo/female) was 1.75/1.0. Eleven patients had minimal disease (stages A, B and AR) and 22 advanced disease (stages C ando). Twenty patients achieved complete remission (61%) and 12 (36%) of them were continuously disease-free. Ten of 11(91%) patients with minimal disease achieved complete remission and had a 33 months survival of 69%; 10/22(45%) patients with advanced disease achieved complete remission with a 33 months survival of 27%. Between the 20 complete remission patients, 7 (35%) recurred; 2 of them at the CNS. Two patients (6%) died with acute tumor cell lysis syndrome and 4 died with direct chemotherapy intoxication; alI of them had advanced disease. This association of Chemotherapy has proved to be very useful in patients with minimal tumor burden but has achieved poor results in patients with massive disease. New associations and dosages are necessary to be studied in this subset of patients.